PENGARUH STRUKTUR MODAL, INTELLECTUAL CAPITAL DAN ENTERPRICE RISK MANAGEMENT DISCLOSURE TERHADAP NILAI PERUSAHAAN (Studi Empiris Pada Perusahaan Property, Real Estate dan Building Construction yang Terdaftar di BEI Periode 2018-2020) - , Julita, Varid Vauzio , Edfan Darlis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
This research aims to analyze the effect of capital structure, intellectual capital, and enterprise risk management disclosure, of firm value. The population in this research is on property, real estate, and building construction  companies which is listed on the Indonesia Stock Exchange (idx) in 2018-2020 consist of 65 companiest. The sample in this research used purposive sampling method so sample total is 40 companiest. Hypothesis analysis used in this variable is using multiple linear regression. The results of this study indicate the capital structure, intellectual capital and   enterprise risk management disclosure does affect of firm value Keywords : Firm Value, Capital Structure, Intellectual Capital, and Enterprise Risk Management Disclosure.